Effect of vibro-milling time and calcination condition on phase formation and particle size of nickel niobate nanopowders - O. Khamman (2018)
The effect of milling time on the phase formation and particle size of nickel niobate, NiNb2O6, powder synthesized by a solid-state reaction via a vibro-milling technique was investigated. Powder samples were characterized using DTA, XRD, SEM and laser diffraction techniques. It was found that the smallest particle size of 32 nm was achieved at 25 h of vibro-milling after which a higher degree of particle agglomeration was observed on continuation of milling to 35 h. In addition, by employing an appropriate choice of the milling time, a narrow particle size distribution curve was also observed. © 2007 Elsevier Ltd and Techna Group S.r.l.